Cyber Sex Sebagai Implikasi Perkembangan Teknologi Komunikasi - Galih Akbar Prabowo (Journal of Communication Studies, 2021)
Along with its development, internet technology brings so many impacts to society. Not only in the way of communicating and seeking information, the development of the internet itself also has an impact on the sexual life of its users. The phenomenon of cybersex as one of the deviations in internet consumption patterns in society is a manifestation of the impact of the development of the internet on a person's sexual life. The existence of the internet have changed the concept of traditional sexuality to be more modern, where now the fulfillment of sexual needs can also be done through virtual activities, not just physical contact. As a result, the internet is now widely used as a tool to satisfying the sexual desires of cybersex perpetrators themselves. And Indonesia, is one of the countries where the cybersex phenomenon is growing so rapidly.